Fungsi Pengawasan DPRD terhadap Penggunaan APBD di Kabupaten Mamuju - Sudarsono, Sudarsono; Kamal, Muhammad; Razak, Askari (CV. Social Politic Genius (SIGn), 2024)
This study aims to gain an in-depth understanding of how the Mamuju Regency House of Representatives carries out its oversight function and its accountability mechanisms over Regional Budget utilization in the Mamuju Regency. The study employs a normative legal research method with a statute approach. The collected legal materials are then analyzed qualitatively to describe the issues and address the research objectives. The results of this study indicate that the oversight function of the Mamuju Regency House of Representatives is an integral element of good local governance. This function is crucial in ensuring the accountability and transparency of Regional Budget utilization as a vital instrument for regional development. The optimization of the Mamuju Regency House of Representatives’s oversight function, including the exercise of the rights of interpellation, inquiry, and expressing opinions, is a determining factor in preventing corruption and guaranteeing the effectiveness of Regional Budget utilization. The accountability mechanisms for Regional Budget management encompass coherent and systematic stages, including the democratic and participatory formulation and enactment of the Regional Budget, the closely monitored implementation by the Mamuju Regency House of Representatives, and the submission of accountability reports and audit reports that present comprehensive evaluations. Therefore, it is recommended that the supporting elements of the Mamuju Regency House of Representatives enhance synergy and coordination in carrying out the oversight function. The Audit Board is expected to improve the quality of audits and expand the scope of audits over Regional Budget utilization. The Regency Government should enhance transparency and accountability in Regional Budget management. Public participation in overseeing Regional Budget utilization must also be enhanced through various mechanisms that facilitate public engagement.